2016
DOI: 10.1097/acm.0000000000001125
|View full text |Cite
|
Sign up to set email alerts
|

Silent Bias: Challenges, Obstacles, and Strategies for Leadership Development in Academic Medicine—Lessons From Oral Histories of Women Professors at the University of Kansas

Abstract: Attaining "full professor" status is the pinnacle of academic success. Women who successfully navigated this academic ladder describe significant external and internal challenges that require multiple strategies to overcome. Leadership development entails a combination of individual support through mentors and sponsors, self-education and reflection, and organizational structural support to promote diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 7 publications
2
8
0
3
Order By: Relevance
“…In the workplace, women were twice as likely as men to attribute discrimination to gender. This is consistent with previous research 7 , 9 , 15 , 17 , 22 that has found that women physicians experience gender discrimination in the workplace. This is especially troubling given that gender discrimination predicts burnout among women physicians, 15 which in turn can lead to women physicians leaving the workforce.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the workplace, women were twice as likely as men to attribute discrimination to gender. This is consistent with previous research 7 , 9 , 15 , 17 , 22 that has found that women physicians experience gender discrimination in the workplace. This is especially troubling given that gender discrimination predicts burnout among women physicians, 15 which in turn can lead to women physicians leaving the workforce.…”
Section: Discussionsupporting
confidence: 93%
“…It is fostered by employees' bias, 2 decisions to reinforce gendered norms even when they are counterproductive, 3 , 4 and the interaction between gender stereotyping and institutional policies. 5 Sexual harassment and gender discrimination in medicine are not new either, as research shows, 6 , 7 and the #MeToo movement has given women physicians a new platform from which to share their experiences and call for change. 1…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The women performed told identities that enumerated negative professional experiences associated with their gender identities. Similar to recent articles which describe how women are not afforded the same authority as men, 17,18 our findings also suggest that women physicians struggle with this bias. The racially/ethnically minoritized physicians also provided examples of facing discrimination, which corroborates previously reported experiences.…”
Section: Discussionsupporting
confidence: 89%
“…In another study, female professors at a medical school described gender-based discrimination (e.g., being ignored) as a significant challenge to their career development (Pingleton, Jones, Rosolowski, & Zimmerman, 2016). They reported coping with discrimination using techniques such as downplaying, keeping a distance, and using humor.…”
Section: Gender Differences and Womenmentioning
confidence: 99%